2020
DOI: 10.1177/1751143720972630
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 ICU remote-learning course (CIRLC): Rapid ICU remote training for frontline health professionals during the COVID-19 pandemic in the UK

Abstract: Background The unprecedented increase in critically ill patients due to the COVID-19 pandemic mandated rapid training in critical care for redeployed staff to work safely in intensive care units (ICU). Methods The COVID-19 ICU Remote-Learning Course (CIRLC) is a remote delivery course developed in response to the pandemic. This was a one-day course focused on the fundamentals of Intensive Care. The course used blended learning with recorded lectures and interactive tutorials delivered by shielding and frontlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…From the eleven research studies included in the review, sample sizes ranged from ten (Marks, Edwards, & Jerge, 2020) to 1269 (Camilleri et al, 2020). One study reported 59% (N=19) of participants were male, and 41% (N=13) female (Payne, Rahman, Bullingham, Vamadeva, & Alfa-Wali, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…From the eleven research studies included in the review, sample sizes ranged from ten (Marks, Edwards, & Jerge, 2020) to 1269 (Camilleri et al, 2020). One study reported 59% (N=19) of participants were male, and 41% (N=13) female (Payne, Rahman, Bullingham, Vamadeva, & Alfa-Wali, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, staff providing care specifically to COVID-19 patients required an introduction to diagnosis and anticipated patient needs. These included prone and positioning, maintaining vascular catheters and dialysis circuits, sedation, and administering vasoactive medication (Camilleri et al, 2020; Doussot et al, 2020; NHS England & NHS Improvement, 2020b). Redeployed staff was also often asked to liaise with families and required training on communicating bad news (Payne et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations